The Vertical Migratory Rhythm of Intertidal Microphytobenthos in Sediment Depends on the Light Photoperiod, Intensity, and Spectrum: Evidence for a Positive Effect of Blue Wavelengths - Barnett, Alexandre; Méléder, Vona; Dupuy, Christine; Lavaud, Johann (Frontiers in Marine Science, 2020)
Estuarine intertidal flats strong biological productivity is mainly based on the activity of benthic microalgae communities or microphytobenthos (MPB), mostly dominated by diatoms. Epipelon is a major MPB growth form comprising motile species, which perform repeated “vertical migration” patterns in the upper sediment layers according to tidal and diurnal cycles with upward migration at the beginning of the daylight emersion and downward migration before immersion starts. Although this fascinating behavior has been extensively studied for more than a century, many of its features remain uncharacterized. Epipelon migratory rhythms are believed to be driven by an endogenous internal clock of unknown nature in combination with diverse environmental stimuli. Among the environmental stimuli impacting on MPB vertical migration, light is probably the most important. Rhythmic changes in surface abundance of natural MPB assemblages were therefore continuously assessed at high frequency by Imaging-PAM fluorimetry in fresh sediment sampled at different seasons, comprising 85 migration profiles from 40 sediment samplings over 2 years, and exposed to different light conditions without any other environmental stimuli (i.e., no tidal-like water flow and stable optimal temperature). In particular, we manipulated (i) the 24-h natural photoperiod MPB that was acclimated to in order to disentangle the tight link between the diurnal and tidal rhythmicity of epipelon migration, and (ii) the light spectrum in order to potentially influence MPB accumulation at the surface of sediment. We found that the migration rhythmicity mapped onto the tidal cycle but that it was modulated, and even overridden, by the diurnal cycle and by the irradiance level during daytime periods with a positive phototactic upward migration up to a certain threshold (in our conditions, 120 μmol photons m–2 s–1 of white light). Also, we found blue wavelengths (465 nm) triggered MPB surface accumulation, as compared to other wavelengths (white, green, and red) in patterns that were intensity-dependent and species-dependent. In particular, we found two species, Navicula spartinetensis and Gyrosigma fasciola, which strongly migrate up under blue light and could potentially be used as model species for further studying the light-responses of intertidal MPB.